'Women and peace': A human rights strategy for the women, peace and security agenda. Issue 4 (December 2017) - Renzulli, Isobel
UN Security Council Resolution 1325 and the successive thematic resolutions together with a variety of reports have shaped the Women, Peace and Security (WPS) agenda. The ensuing policies and institutional responses try to deal with a variety of issues including women's participation in peace-making initiatives and protection from sexual violence during armed conflict and in its aftermath. As such these responses are underpinned by a reactive approach with a focus on conflict and post-conflict gender-sensitive areas of intervention. While these remain worthwhile interventions, the WPS agenda, in spite of its name, inadequately addresses gender-sensitive areas in peace situations, regardless of the existence of conflicts. Building on feminist critiques of the WPS agenda and the findings and recommendations of the 2015 UN Global study on the implementation of Resolution 1325, the article argues that the WSP agenda and its prevention limb need to elaborate and integrate more explicitly and comprehensively a human rights strategy that shifts the focus from a reactive to a proactive model, one which pursues gender equality and women's human rights in its own right, irrespective of whether conflicts erupt or not. A human rights infused WPS preventive agenda should be premised, on the one hand, on a clear understanding and endorsement of the meaning of gender equality, on the other hand, on the creation of mechanisms and process bolstering the role of international and regional human rights regimes. In particular, robust regional human rights systems have the potential to create fora for the participation of and interaction with domestic constituencies in the region. This in turn could lead to the elaboration of context sensitive, participatory solutions, grounded in international human rights law, to existing forms of discrimination against women, which during conflicts may be exacerbated, for example, in the form of sexual enslavement and abductions as reported in recent and less recent conflicts.